2013
DOI: 10.1371/journal.pone.0080292
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Cell Expression of Vascular Endothelial Growth Factor Receptor 2 Is an Adverse Prognostic Factor in Patients with Squamous Cell Carcinoma of the Lung

Abstract: A robust immunohistochemical (IHC) assay for VEGFR2 was developed to investigate its utility for patient tailoring in clinical trials. The sensitivity, specificity, and selectivity of the IHC assay were established by siRNA knockdown, immunoblotting, mass spectrometry, and pre-absorption experiments. Characterization of the assay included screening a panel of multiple human cancer tissues and an independent cohort of non-small cell lung carcinoma (NSCLC, n = 118) characterized by TTF-1, p63, CK5/6, and CK7 IHC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 61 publications
3
40
2
1
Order By: Relevance
“…Overexpression of VEGFR2 is associated with invasion and metastasis in lung cancer. In present study, 80.5% of cases showed positive expression of VEGFR2, which was similar to previous study [38]. The high prevalence of overexpression of VEGFR2 demonstrated that VEGFR2 overexpression was a common event in tumorigenesis of SqCLC.…”
Section: Discussionsupporting
confidence: 91%
“…Overexpression of VEGFR2 is associated with invasion and metastasis in lung cancer. In present study, 80.5% of cases showed positive expression of VEGFR2, which was similar to previous study [38]. The high prevalence of overexpression of VEGFR2 demonstrated that VEGFR2 overexpression was a common event in tumorigenesis of SqCLC.…”
Section: Discussionsupporting
confidence: 91%
“…An independent IHC assay using the D13C6 antibody was developed following an assay development paradigm previously described. 33 This assay demonstrated a wider range of staining intensities from negative immunoreactivity (OVCAR8), through light cytoplasmic immunoreactivity (M059K), to more intense staining (MG63, Fig. 2C).…”
Section: Immunoblot Profiles and Ihc Profiles Differed When Comparingmentioning
confidence: 90%
“…Histotechnological preparation of cell lines was performed as described previously. 33 For staining, formalin-fixed and paraffin-embedded (FFPE) cell line blocks were punched and 1-mm cores were delivered to a recipient cell microarray block using TMAjr (Pathology Devices, Westminster, MD).…”
Section: Control Cell Lines Cell Culture and Histotechnological Prementioning
confidence: 99%
“…In recent years, these methodologies have been utilized to characterize the heterogeneity of tumor angiogenesis programs in various histologic and clinical subtypes of human cancers [14–19]. Previously, we demonstrated immunohistochemical expression of VEGFR2 protein and vascular phenotypes in human breast carcinomas [15].…”
Section: Introductionmentioning
confidence: 99%